Mathematically and experimentally defined porous bone scaffold produced for bone substitute application - Yekta, Hamed Joneidi; Shahali, Maryam; Khorshidi, Siros; Rezaei, Soheila; Montazeran, Amir Hussein; Samandari, Saeed Saber; Khandan, Amirsalar (Mashhad Univ Med Sciences, 2018)
Objective (s): Artificial bone implants have been studied as a possible bone replacement for fractured and destroyed facial tissue; the techniques employed to determine the success of the dental implants. The stability, porosity and resistance of the bone implant which is subjected to varying forces and stresses within the surrounding bone is a subject of interest among the dentists. Materials and Methods: An experimental analysis was conducted on bio-nanocomposite scaffold using space holder methods. The reaction of the bio-nanocomposites deformation under load was determined using Abaqus software. Thereafter, an analytical solution was presented to express explicitly the deformation responses of the artificial bone implant. Results: It was seen that the vibrational behavior and mechanical performance of the sample containing 15 wt% additives have shown better mechanical characteristic compared to the pure specimen. On the other hand, the additive weight fraction has a significant effect on the compression test and porosity value. Also, the elastic modulus of the samples increases more than two times with the addition of additive (from 60 MPa to 145 MPa). From the results, it can be concluded that the highest vibration variation is seen in the sample with lower MNPs percentages. Conclusion: By observing the results of the stresses, it was seen that the stresses were in a small value in the bio-nanocomposites with highest amount of reinforcement.
Keywords: Abaqus; Nanocomposite; Porous bone implant; Scaffold; Stress analysis